Something Borrowed, Something New: A Governance and Social Construction Framework to Investigate Power Relations and Responses of Diverse Stakeholders to Policies Addressing Antimicrobial Resistance - Helena Legido-Quigley; Mishal S. Khan; Anna Durrance-Bagale; Johanna Hanefeld (MDPI AG, 2018)
While antimicrobial resistance (AMR) has rapidly ascended the political agenda in numerous high-income countries, developing effective and sustainable policy responses in low- and middle-income countries (LMIC) is far from straightforward, as AMR could be described as a classic ‘wicked problem’. Effective policy responses to combat AMR in LMIC will require a deeper knowledge of the policy process and its actors at all levels—global, regional and national—and their motivations for supporting or opposing policies to combat AMR. The influence of personal interests and connections between for-profit organisations—such as pharmaceutical companies and food producers—and policy actors in these settings is complex and very rarely addressed. In this paper, the authors describe the role of policy analysis focusing on social constructions, governance and power relations in soliciting a better understanding of support and opposition by key stakeholders for alternative AMR mitigation policies. Owing to the lack of conceptual frameworks on the policy process addressing AMR, we propose an approach to researching policy processes relating to AMR currently tested through our empirical programme of research in Cambodia, Pakistan, Indonesia and Tanzania. This new conceptualisation is based on theories of governance and a social construction framework and describes how the framework is being operationalised in several settings.